Manipulating exchange bias in Co/IrMn films by surface acoustic wave. (22nd December 2022) - Qiao, Huifang; Niu, Yabin; Li, Xiaolei; Mi, Shuai; Liu, Xindan; Xue, Jiangtao; Wu, Shuxuan; Wang, Xiangqian; Liu, Qingfang; Wang, Jianbo
Abstract: Exchange bias (EB) has extremely important applications in spintronics, researchers have proposed various means to manipulate it. This work realizes the regulation of the EB field in Co/IrMn films sputtered on LiNbO3 substrate by the surface acoustic wave (SAW). The experimental results show that in the out-of-plane and in-plane EB of Co/IrMn films, both the coercivity and the EB field decrease with the increase of the SAW power. The dynamic strain field provided by the SAW transfer to the magnetic films changes the arrangement of the magnetic moments in the Co layer and IrMn layer, the rearrangement of magnetic moments leads to a reduction in the EB field. Our experiments provide an approach to manipulate the EB field, opening a potential avenue for manipulating antiferromagnetic moments in the future.